Tidal and wave energy and technology investigation in Singapore - Zhou, Youcai. (2011)
This study finds that Wave Activated Bodies (WAB) wave technology most suitable for use in Singapore. Four WAB technology devices were compared and the Oyster WAB device was selected for use in Singapore. The Oyster WAB device requires less stringent operating conditions, the technology is mature, and it performs better in terms of output power in Singapore coastal conditions.